DOP58 Tofacitinib for ulcerative colitis: Results of the ICC Registry, a nationwide prospective observational cohort study. (15th January 2020) - Biemans, V B; Sleutjes, J A M; de Vries, A C; Bodelier, A G; Dijkstra, G; Oldenburg, B; Löwenberg, M; van Bodegraven, A A; van der Meulen-de Jong, A E; de Boer, N K; Srivastava, N; West, R L; et al.
Abstract: Background: Tofacitinib is a janus kinase 1 and 3 inhibitor approved for the treatment of ulcerative colitis (UC). Real-world evidence is needed to evaluate the effectiveness, usage and safety in daily practice. Methods: UC patients in whom tofacitinib was started in 15 hospitals (8 academic, 7 non-academic) participated in the ICC Registry : a Dutch prospective, observational registry. Visits were planned at baseline, Week 12, and 24. Patients with both clinical (Short Clinical Colitis Activity Index (SCCAI) >2) and objective disease activity (endoscopy (Mayo >0), C-reactive protein (CRP) >5 mg/l or faecal calprotectin (FCP) >250 µg/g) were included. In this study, corticosteroid-free clinical remission (SCCAI ≤2), biochemical remission (FCP ≤250 µg/g), combined corticosteroid-free clinical and biochemical remission, predictors of remission, safety outcomes, dose optimisation, and effect on lipids were determined at Week 24. Only patients from centres with routine endoscopic follow-up (regardless of symptoms) were analysed to determine endoscopic remission (Mayo = 0) at Week 12. All analyses were done on an intention-to-treat basis. Results: In total, 111 UC patients (95% anti-TNF, 60% vedolizumab, 4% ustekinumab exposed) were followed for a median of 24 weeks (IQR 12–26). All patients had both active clinical and objective disease (SCCAI 8 (IQR 5–11), FCP 1800µg/g (IQR 633–2682)). Corticosteroid-free clinical, biochemical, and combined corticosteroid-free clinical and biochemical remission rate at week 24 was 29%, 25%, and 19%, respectively. Endoscopic remission was achieved in 21% of patients ( n = 33) at Week 12. Prior vedolizumab exposure was associated with a lower remission rate at week 24 (OR 0.33, 95% CI 0.11–0.94) in multivariable analysis. In total, 36 patients (88 per 100 patient-years) experienced tofacitinib-related adverse events (most common: cutaneous lesions and headache) of which 6 patients (18 per 100 patient-years) discontinued treatment. No thromboembolic events were reported. We observed 4 cases of herpes zoster re-activation but no severe infections (requiring hospitalisation). During follow-up 14 hospitalisations and 5 (4.5%) colectomies were performed. Cholesterol, HDL, and LDL increased between baseline and week 12 (18% (95% CI 9–26, n = 35), 18% (95% CI 8–28, n = 35) and 27% (95% CI 14–39, n = 35), respectively). At week 24, 33% of patients used 10 mg twice daily. Conclusion: Tofacitinib is an effective treatment for UC after anti-TNF and/or vedolizumab failure. We did observe a relatively high rate of adverse events in this refractory UC cohort.